Autologous decellularized extracellular matrix protects against H2O2-induced senescence and aging in adipose-derived stem cells and stimulates proliferation in vitro. Issue 5 (21st May 2019) - Yu, Xiaofang; He, Yucang; Chen, Zhuojie; Qian, Yao; Wang, Jingping; Ji, Ziwan; Tan, Xiaoyan; Li, Liqun; Lin, Ming
Abstract : Background: Adipose-derived stem cells have attracted significant interest, especially in stem cell therapy and regenerative medicine. However, these cells undergo gradual premature senescence in long-term cultures, which are essential for clinical applications that require cell-assisted lipotransfer or tissue repair.Methods: Since the extracellular matrix forms the microenvironment around stem cells in vitro and regulates self-renewal and multipotency in part by slowing down stem cell aging, we evaluated its potential to protect against senescence, using H2 O2 -induced adipose-derived stem cells as a model.Results: We found that supplementing cultures with decellularized extracellular matrix harvested from the same cells significantly promotes proliferation and reverses signs of senescence, including decreased multipotency, increased expression of senescence-associated β-galactosidase, and accumulation of reactive oxygen species.Conclusion: These findings suggest a novel approach in which an autologous decellularized extracellular matrix is used to prevent cellular senescence to enable the use of adipose-derived stem cells in regenerative medicine.